2015
DOI: 10.18343/jipi.20.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Zooplankton Community Structure in Jakarta Bay

Abstract: The dynamics in zooplankton abundance were regulated by changes in water physical-chemical parameters and interaction with biotic factors. In this research we examined the relationship between zooplankton community dynamic and important biotic factors, such as predation and food availability, in Jakarta bay. Plankton samplings were done in 10 sampling stations in Jakarta bay, from July to November 2009. Zooplankton samples were collected using horizontal towing method with NORPAC plankton net (mesh size 300 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
4
0
2
Order By: Relevance
“…The DO content of water >5 mg/L is good for phytoplankton and zooplankton [47]. This is in line with the opinion of Damar et al [48], that the high abundance of phytoplankton can contribute to high levels of dissolved oxygen, which is the result of the photosynthesis process.…”
Section: Rawapening Lake Diatom Community Structuresupporting
confidence: 79%
“…The DO content of water >5 mg/L is good for phytoplankton and zooplankton [47]. This is in line with the opinion of Damar et al [48], that the high abundance of phytoplankton can contribute to high levels of dissolved oxygen, which is the result of the photosynthesis process.…”
Section: Rawapening Lake Diatom Community Structuresupporting
confidence: 79%
“…Water quality parameters are in the optimal range, particularly temperature (29.3 o C), salinity (30ppt), and pH (7.7) (Table 4). For the growth rate of phytoplankton, some references stated the optimum salinity is 25 -32 ppt (Nybakken, 1992), the optimal temperature is 20 -32 o C (Effendi, 2003; Kusumaningtyas et al, 2014;Kadir et al, 2015), and the optimal pH value range is 7 -8.5 (Berge et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found that water temperature ranged from 34.33 to 38.67 0 C; the highest temperature was in the palm oil mill. Water temperature for phytoplankton and zooplankton ranged, respectively, from 25-30 0 C and 15-35 0 C ( Kadir et al, 2015). The findings showed a temperature distribution which exceeded deviation 3 and was heterogeneous; the condition was not optimum temperature for phytoplankton growth but on the other hand, it was good for zooplankton growth.…”
Section: Fig 3 Zooplankton's Diversity Uniformity and Dominancementioning
confidence: 94%